INTEGRATIVE AND COMPLEMENTARY PRACTICES FOR PERFORMING ONCOTIC CYTOLOGY IN PRIMARY HEALTH CARE - Silva de Araújo, Maria Eduarda (Revista de Ciências da Saúde Nova Esperança, 2024)
Cervical cancer has high morbidity and mortality rates worldwide. The Pap smear is responsible for around 80% of early cancer detection, but there is low adherence to the test, related to cultural, social, psychological and economic factors that affect timely detection and the reduction of mortality from this cancer. The aim of this study is to analyze the use of music therapy and aromatherapy in the performance of oncotic cytology for women. This is a descriptive, exploratory study with a qualitative approach, carried out in a municipality in the interior of Rio Grande do Norte, between July and October 2023. The age group included was women aged between 18 and 64, and the sample consisted of 15 women. Data was collected using a semi-structured questionnaire. The information obtained was analyzed by content, according to Bardin. Fifteen women aged between 21 and 63 took part in the study. Results are divided into two categories: women's feelings about taking the preventive exam; participants' perceptions of the exam using the Integrative and Complementary Practices used in the study. The participants, despite knowing the importance of taking the exam periodically, for various reasons, do not carry it out as recommended. Feelings such as shame and tension are factors that influence adherence to the preventive exam and interfere with the search for services. Therefore, the use of Integrative and Complementary Practices is effective when it aims to build humanized care and form a bond between professional and patient.